2004
DOI: 10.1079/bjn20041099
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the impact of nutrition education on growth indices of Iranian nomadic children: an application of a modified beliefs, attitudes, subjective-norms and enabling-factors model

Abstract: In order to teach suitable feeding and hygiene practices to a group of randomly selected Qashqa'i tribe families with 406 children aged 0 -59 months, a culturally appropriate community-based education intervention approach was used. To assess the impact of the intervention on the study group, another group of families with 405 children were randomly selected to serve as the controls. At the beginning of the intervention programme both groups of children had access to a similar diet, consisting of cereals, bean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
67
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(74 citation statements)
references
References 8 publications
5
67
2
Order By: Relevance
“…The study showed significant differences between the intervention and control group on WAZ, WHZ and HAZ after 12-month nutrition education (Salehi, et al, 2004). A study conducted in Pakistan documented that the mean (SD) weight for age and weight for height Z-scores of children were significantly higher in the intervention group compared to those in the control group.…”
Section: Discussionmentioning
confidence: 98%
“…The study showed significant differences between the intervention and control group on WAZ, WHZ and HAZ after 12-month nutrition education (Salehi, et al, 2004). A study conducted in Pakistan documented that the mean (SD) weight for age and weight for height Z-scores of children were significantly higher in the intervention group compared to those in the control group.…”
Section: Discussionmentioning
confidence: 98%
“…Educational programs can lead to improved child nutrition, in the absence and presence of diarrhea. 38,39 To shed light on whether an educational intervention could improve caregivers' intended practices, we piloted a brief educational intervention. The intervention was similar to those previously used in other projects, such as home visits by field-workers and distribution of educational leaflets.…”
Section: Breast Milkmentioning
confidence: 99%
“…From the welfare view, it can also boost the work ambition of employee (13). The importance of nutrition education programs depends on the level of their effectiveness (14). Nutrition education programs can be more effective if they are supported by a model or theory specifically addressing changes in nutrition behavior (15).…”
Section: Introductionmentioning
confidence: 99%
“…Subjective norms are a component of the TPB and refer to an individual's perception about a particular behavior influenced by the judgment of others, including family members (especially spouse), employer, health experts, and friends (36). If the key members of life (especially spouses) agree to perform certain healthy behaviors, then it is more likely that the patient will engage in such behaviors (14). Shafieinian et al, also reported that the TPB-based intervention aimed at promoting physical activity had no effect on the subjective norms of the study participants, which were both consistent with the results of the current study (28).…”
mentioning
confidence: 99%